Impact of COVID-19 on the Construction Sector: An Overview - Elizalde, Ruben Rodríguez (Scientific Research, New Technologies and Applications Vol. 3, 2024)
This paper examines the impact of COVID-19 on the construction industry. This book chapter is driven by the high vulnerability of construction workers to the spread of the virus. Due to the unique nature of the construction industry and the specific characteristics of its work procedures, remote work is largely impractical for most activities. Additionally, in light of the sector's significant economic importance, most state and national governments designated construction as an essential activity. The working conditions in this field are distinctive: frequent group travel to job sites, close proximity during work, group accommodations away from home, and meals in restaurants or work canteens. These factors contributed to a high rate of transmission during the pandemic. Even now, construction remains one of the most hazardous sectors in terms of virus transmission. This article discusses the challenges in reducing the spread of the virus among construction workers, outlines how to assess the exposure risk levels associated with different construction tasks, and suggests possible protective measures for various levels of exposure risk.